Biochar as potential precursors for activated carbon production: parametric analysis and multi-response optimization - Rashidi, N.A. (Springer, 2020)
Accelerating greenhouse gas emission particularly carbon dioxide (CO2) in the atmosphere has become a major concern. Adsorption process has been proposed as a promising technology for CO2 adsorption from flue gas, and the carbonaceous adsorbent is a potential candidate for CO2 adsorption at atmospheric pressure and ambient temperature. Biochar derived from palm kernel shell waste was applied as a potential precursor for activated carbon production. This research study employed the response surface methodology coupled with Box-Behnken design to optimize the parameters involved in producing exceptional activated carbon with high yield (Y1) and CO2 adsorptive characteristics (Y2). Specifically, parameters studied include the activation temperature (750â950Â Â°C), holding time (60â120Â min), and CO2 flow rate (150â450Â mL/min). The activated carbon at the optimum conditions was characterized using various analytical instruments, including elemental analyzer, nitrogen (N2) physisorption analyzer, and field emission scanning electron microscopy. Overall, utilization of biochar as the activated carbon precursor is practical compared with the traditional non-renewable materials, due to its cost efficiencies and it being more environment-friendly ensuring process sustainability. Besides, this research study that incorporates physical activation with CO2 as the activating agent is attractive, because it directly promotes CO2 utilization and capture, in addition to the absence of any chemicals that may result in the secondary pollution problems. Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.